2002
DOI: 10.1074/jbc.c100681200
|View full text |Cite
|
Sign up to set email alerts
|

Proton Relay Mechanism of General Acid Catalysis by DNA Topoisomerase IB

Abstract: Type IB topoisomerases cleave and rejoin DNA through a DNA-(3-phosphotyrosyl)-enzyme intermediate. A constellation of conserved amino acids (Arg-130, Lys-167, Arg-223, and His-265 in vaccinia topoisomerase) catalyzes the attack of the tyrosine nucleophile (Tyr-274) at the scissile phosphodiester. Previous studies implicated Arg-223 and His-265 in transition state stabilization and Lys-167 in proton donation to the 5-O of the leaving DNA strand. Here we find that Arg-130 also plays a major role in leaving group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
66
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 25 publications
7
66
0
Order By: Relevance
“…Mutational studies of Arg-130 in vaccinia virus topoisomerase suggested that this residue makes a bidentate contact with DNA (26), which was confirmed by crystal structures showing that Arg- 130 hydrogen bonds to a nonbridging oxygen of the pentavalent transition state and to the 5Ј leaving group oxygen (27,28). This second contact suggested that Arg-130 may play an additional role in proton relay to the 5Ј hydroxyl of the leaving DNA strand (27,30). Although the active site of Topo-V is different from the type IB active site, the two arginines (Arg-130 of vaccinia viral topoisomerase and Arg-131 of Topo-V) are located in nearly identical positions with respect to the tyrosine.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Mutational studies of Arg-130 in vaccinia virus topoisomerase suggested that this residue makes a bidentate contact with DNA (26), which was confirmed by crystal structures showing that Arg- 130 hydrogen bonds to a nonbridging oxygen of the pentavalent transition state and to the 5Ј leaving group oxygen (27,28). This second contact suggested that Arg-130 may play an additional role in proton relay to the 5Ј hydroxyl of the leaving DNA strand (27,30). Although the active site of Topo-V is different from the type IB active site, the two arginines (Arg-130 of vaccinia viral topoisomerase and Arg-131 of Topo-V) are located in nearly identical positions with respect to the tyrosine.…”
Section: Discussionmentioning
confidence: 72%
“…During catalysis, the tyrosine acts as a nucleophile and attacks the scissile phosphate, whereas the two arginines and the histidine are responsible for stabilizing the pentavalent transition state (11,(25)(26)(27)(28)(29). One of the arginines and the lysine are the general acid facilitating proton flow for the DNA cleavage reaction, along with a network of water molecules (27,30).…”
mentioning
confidence: 99%
“…The individual catalytic residues Arg-130, Lys-167, Arg-223, and His-265 accelerate the chemical step by factors of 10 5 , 10 4 , 10 5 , and 10 2 , respectively (13)(14)(15). Lys-167 and Arg-130 comprise a proton relay that catalyzes the expulsion of the 5Ј-O of the leaving DNA strand (19,21). His-265 donates a hydrogen bond to the nonbridging pro-Sp oxygen of the scissile phosphodiester to stabilize the transition state (16,56).…”
Section: Resultsmentioning
confidence: 99%
“…The active sites of poxvirus and nuclear type IB topoisomerases consist of five conserved functional groups, e.g. Arg-130, Lys-167, Arg-220, His-265, and Tyr-274 in vaccinia virus topoisomerase IB (vaccinia TopIB), which execute the cleavage and religation transesterification steps of the catalytic cycle (13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…(The Tp2 nucleotide is defined as the ϩ1 nucleotide.) Four conserved amino acids (Arg-130, Lys-167, Arg-223, and His-265) are responsible for catalyzing the attack of the active site tyrosine (Tyr-274) on the scissile phosphodiester to form the covalent intermediate (2)(3)(4)(5)(6). Biochemical and structural studies suggest that recognition of the 5Ј-CCCTT/3Ј-GGGAA sequence triggers conformational changes in the enzyme that recruit the full set of catalytic side chains into the active site, a process that entails protein contacts with several of the nucleotide bases and specific atoms of the phosphate backbone of DNA within and immediately flanking the CCCTT element (7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%